My Advocacy Embraces Patients: A Case Study of Activist Support for Homeless Persons with Mental Disorders - Wulandari, Virine; Rudangta Arianti (Jurnal Kesehatan dan Kedokteran, 2025)
Homeless individuals with mental disorders (ODGJ) are part of a vulnerable population that frequently experiences social discrimination, rejection from their immediate environment, and difficulties in accessing healthcare facilities. This study aims to identify the forms of social assistance provided by mental health activists and the challenges encountered in supporting homeless ODGJ in the Special Region of Yogyakarta. A qualitative case study approach was employed to examine the experiences of two volunteers selected through purposive sampling. Data were collected via semi-structured interviews and direct observation, then analyzed using thematic analysis. The study reveals two main obstacles faced by participants: (1) resistance from patients' families, including denial of mental health conditions and even physical rejection, and (2) tensions within the participants' own families. The developed solutions include educational approaches, collaboration with community leaders, and dialogue with families. Additionally, this research identifies four categories of support provided: (a) emotional (companionship and confidence-building), (b) appreciative (promotion of creative works and recognition), (c) instrumental (vocational training and medical services), and (d) informational (counseling on therapy and mental disorder management).